CSIG-07. ACTIVATION OF THE ADHESION G PROTEIN-COUPLED RECEPTOR GPR133 BY ANTIBODIES AGAINST THE N-TERMINUS. (12th November 2021) - Stephan, Gabriele; Frenster, Joshua; Ravn-Boess, Niklas; Bready, Devin; Wilcox, Jordan; Schöneberg, Torsten; Liebscher, Ines; Placantonakis, Dimitris
Abstract: We recently demonstrated that GPR133 (ADGRD1), a member of the adhesion G protein-coupled receptor (aGPCR) family, is necessary for growth of glioblastoma (GBM) and is de novo expressed in GBM relative to normal brain tissue. We therefore postulate that GPR133 represents a novel target in GBM, which merits development of therapeutics. Like most aGPCRs, GPR133 is characterized by an intracellular C-terminus, 7 plasma membrane-spanning α-helices and a large extracellular N-terminus. The N-terminus possesses a conserved GPCR autoproteolysis-inducing (GAIN) domain that catalyzes cleavage at a GPCR proteolysis site (GPS), resulting in a C-terminal fragment (CTF) and an N-terminal fragment (NTF). We showed that dissociation of the cleaved NTF and CTF at the plasma membrane increases canonical signaling of GPR133, which is mediated by coupling to Gs and increase in cytosolic cAMP. Toward characterizing the effect of biologics on GPR133 function, we overexpressed wild-type or mutant forms of GPR133 in HEK293T cells and patient-derived GBM cells lines. Treatment of these cells with antibodies specifically targeting the NTF of GPR133 increased receptor activation in a dose-dependent manner. No effects were elicited with an antibody against the receptor's intracellular C-terminus. Interestingly, cells overexpressing a cleavage-deficient mutant GPR133 (H543R) did not respond to antibody stimulation, suggesting that the effect is cleavage-dependent. Following antibody treatment, co-purification of the GPR133 NTF and the N-terminal antibody from the cell culture supernatant indicated the formation of antibody-NTF complexes. Analysis of these complexes suggested that antibody binding stimulated the dissociation of the NTF from the CTF. However, the increased flexibility of the GAIN domain and NTF after cleavage, independently of dissociation, may also endow the receptor with responsiveness to the effects of the antibodies. These data constitute a proof-of-concept paradigm of modulation of GPR133 function with antibodies. This work provides rationale for pursuing development of biologics targeting GPR133 in GBM.